2015
DOI: 10.1242/dev.129841
|View full text |Cite
|
Sign up to set email alerts
|

Maternal BCAS2 protects genomic integrity in mouse early embryonic development

Abstract: Mammalian early embryos maintain accurate genome integrity for proper development within a programmed timeline despite constant assaults on their DNA by replication, DNA demethylation and genetic defects transmitted from germ cells. However, how genome integrity is safeguarded during mammalian early embryonic development remains unclear. BCAS2 (breast carcinoma amplified sequence 2), a core component of the PRP19 complex involved in pre-mRNA splicing, plays an important role in the DNA damage response through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 62 publications
(64 reference statements)
6
43
0
Order By: Relevance
“…In contrast, npm2b appears to function at a later stage or other factors can replace its role in the early stages as the npm2b -deficient embryos are capable of dividing until around 4 hpf, which corresponds to previous reports [8,14]. These findings are in line with those demonstrated for other maternal-effect genes in mammals, such as mater , floped , filia , tle6 [47], and bcas2 [48] as well as in zebrafish, including fue [49] and cellular atoll [50], all of which function to moderate the early events of fertilization and embryogenesis and their ablation leads to arrest and mortality at the earliest stages of embryogenesis.…”
Section: Expression Domains Of Npm2a and Npm2b In Vertebratessupporting
confidence: 89%
“…In contrast, npm2b appears to function at a later stage or other factors can replace its role in the early stages as the npm2b -deficient embryos are capable of dividing until around 4 hpf, which corresponds to previous reports [8,14]. These findings are in line with those demonstrated for other maternal-effect genes in mammals, such as mater , floped , filia , tle6 [47], and bcas2 [48] as well as in zebrafish, including fue [49] and cellular atoll [50], all of which function to moderate the early events of fertilization and embryogenesis and their ablation leads to arrest and mortality at the earliest stages of embryogenesis.…”
Section: Expression Domains Of Npm2a and Npm2b In Vertebratessupporting
confidence: 89%
“…(3) the DNA replication in the zygote is accompanied by drastic genome remodeling, including massive DNA demethylation, histone modifications and histone replacement (Akiyama et al, 2011;Murai et al, 2014;Swiech et al, 2007;Xu et al, 2015). It has been proposed that genome remodeling after fertilization, particularly in the male nucleus, induces DNA damage including both single-and doublestrand breaks (Hajkova et al, 2010;Nakatani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of the BCAS2/spf27 subunit destabilizes the hPrp19 complex, which results in mitotic defects 9 . BCAS2 was recently found to be an essential gene during the embryonic stage 10 . We previously reported that wing-specific knockdown of BCAS2 causes Drosophila wing developmental defects 11 ; due to BCAS2 participates in Delta pre-mRNA splicing and regulates the Delta-Notch signaling 12 .…”
mentioning
confidence: 99%